PERAN KEPEMILIKAN MANAJERIAL MEMODERASI PENGARUH GROWTH OPPORTUNITY, FIRM SIZE, DAN RISIKO LITIGASI TERHADAP PRUDENCE ACCOUNTING - Afifah, Desita Nur; Zulaecha, Hesty Erviani (STIE Mahardhika, 2026)
This study aims to examine the effect of growth opportunity, firm size, and litigation risk on accounting prudence, with managerial ownership as moderating variable. A quantitative approach is employed using secondary data from companies in the consumer cyclicals sector, statistical analysis is conducted to test direct relationship among variables and the moderationg role of managerial ownership. The result indicate that growth opportunity has a negative but insignifficant effect on accounting prudence, suggesting that firm with high growth prospect tend to present more optimistic financial reporting. Firm size has a positive and siginifficant effect on accounting prudence, indicating that large firm apply greater conservatism due to stornger external monitoring and higer transparency demands. Litigation risk does not signifficantly affect accounting prudence. Futhermore, managerial ownership signifficantly moderates the relationship between growth opportunity and accounting prudence, as well as strengthes the positives effect on firm size on accounting prudence. However, it does not moderate factors, particulary firm size and managerial ownership structure, play a more dominant role in determining accounting prudence than external factors.